The indirect effect of servant leadership on employee attitudes through diversity climate in selected South African organisations - Sean McCallaghan (SA Journal of Human Resource Management, 2020)
Orientation: Organisations are continuously diversifying their workforces and require information on how to benefit from positive diversity-related outputs. Servant leadership might provide a solution to improve diversity-related outputs. Literature proposes that servant leadership, diversity climate and employee outputs are related; yet, literature is silent on how these observations would operate in a transitional environment where organisations are intentionally attempting to correct inherited workforce imbalances. Research purpose: The study examined indirect effects of diversity climate on the relationship between servant leadership and employee attitudes. Motivation for the study: Examinations of the indirect effects of diversity climate are limited. Method: A quantitative approach with cross-sectional design collected 230 responses from a convenience sample. Respondents completed assessments for servant leadership, diversity climate, organisational commitment, job satisfaction and intention to quit. Statistical analysis included descriptive statistics, correlational analysis and three independent mediation models. Main findings: Servant leadership and diversity climate are positively associated with organisational commitment, job satisfaction, and non-intention to quit. Servant leadership demonstrated a direct effect on diversity climate, organisational commitment, job satisfaction and non-intention to quit. Diversity climate had a positive impact on organisational commitment. Servant leadership demonstrated an indirect effect on organisational commitment via diversity climate. Practical implications: The improvement of organisational commitment cannot only rely on servant leadership; a conducive diversity climate is also required. Contribution and value-added: The examination contributes towards limited diversity climate research with evidence of the indirect capacity of diversity climate.